Fossilized ontogenies: The contribution of placoderm ontogeny to our understanding of the evolution of early gnathostomes - Johanson, Z.; Trinajstic, Katherine (Wiley-Blackwell Publishing Ltd., 2014)
Placoderms, representing phylogenetically more inclusive jawed vertebrates and successive sister taxa to crown-group gnathostomes, are critical to our understanding of character evolution within the crown-group (chondrichthyans + osteichthyans), including developmental characters. Early ontogenetic stages of placoderms are generally poorly known, although some exceptional faunas preserve both embryonic (e.g. from the Gogo Formation, Western Australia) and post-embryonic individuals (the Miguasha Formation, Canada; Lode Formation, Latvia; Merriganowry Formation, Gogo Formation, Australia). Information provided by these ontogenies is relevant to questions of placoderm taxonomy and phylogeny, but also to broader questions pertinent to vertebrate evolution as a whole, for example, evolution of bone development, evolution of the axial skeleton and evolution of reproduction.